2018
DOI: 10.14740/jh367w
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Hematological Parameters, Hemoglobin and Hematocrit With Liver Enzymes, Aspartate Transaminase and Alanine Transaminase Among Patients With Chronic Kidney Disease Undergoing Hemodialysis in Aljouf Region, Saudi Arabia

Abstract: Background: Anemia results from low kidney production of the erythropoiesis-stimulant erythropoietin. Good liver function is crucial to patients with chronic kidney disease (CKD). This study analyzed two hematological parameters (hemoglobin (Hb) and hematocrit (Ht)) and two liver enzymes, alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in patients with CKD undergoing hemodialysis (HD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This may be one of the potential mechanisms by which anemia or an obvious decrease in serum hemoglobin is prevalent in PLWHA. Another study suggested that anemia may have resulted from insufficient production of erythropoiesis-stimulant erythropoietin in the kidney ( 26 ). Subsequently, it is noteworthy that ferritin is an important iron-containing protein ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be one of the potential mechanisms by which anemia or an obvious decrease in serum hemoglobin is prevalent in PLWHA. Another study suggested that anemia may have resulted from insufficient production of erythropoiesis-stimulant erythropoietin in the kidney ( 26 ). Subsequently, it is noteworthy that ferritin is an important iron-containing protein ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, values of transaminase are lower in cases with chronic renal failure (CRF) whether or not they are dialysis-dependent [34]. This is attributed to several reasons among which is hemodilution, insufficiency in many cofactors in CKD patients such as, vitamin B6, pyridoxine, NADPH, and the presence of uremic factors that inhibit transaminase activity [35,36].…”
Section: Discussionmentioning
confidence: 99%